2013
DOI: 10.1111/bjep.12009
|View full text |Cite
|
Sign up to set email alerts
|

Reading and listening comprehension and their relation to inattention and hyperactivity

Abstract: These results indicate that the reading comprehension problems of children with attention difficulties are related to poor word reading and that listening comprehension is particularly vulnerable in children at risk of ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 71 publications
2
42
2
2
Order By: Relevance
“…Although basic reading skills tend to be relatively preserved in children with ADHD alone, attention problems can impact their reading performance, even if at a subclinical level (Ghelani et al, 2004; Cain and Bignell, 2014). This is particularly true of reading fluency and comprehension.…”
Section: Introductionmentioning
confidence: 99%
“…Although basic reading skills tend to be relatively preserved in children with ADHD alone, attention problems can impact their reading performance, even if at a subclinical level (Ghelani et al, 2004; Cain and Bignell, 2014). This is particularly true of reading fluency and comprehension.…”
Section: Introductionmentioning
confidence: 99%
“…After each story the children answered eight multiple-choice questions. The internal consistency of this adapted measure is good (Cronbach's α = .84), and scores relate to reading comprehension assessed by the Neale administered in its traditional format (Cain & Bignell, 2014). The Gates-MacGinitie is a groupadministered test, in which children are required to select a synonym of a given word from one of four options.…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of whether students have been formally identified with ADHD or not, if they display inattention and/or hyperactivity they are likely at high risk for poor academic achievement and school dropout (Breslau et al, 2009;Currie & Stabile, 2006;Fletcher & Wolfe, 2008). Particularly, children with ADHD also often have significant difficulties with their reading and writing (Cain, & Bignell, 2014;Tannock, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, Carroll et al (2005) found that the association between ADHD and reading difficulties primarily reflected increased symptoms of inattention. It is interesting to note that students with ADHD who do not have coexisting reading disorders have also been found to exhibit relative weaknesses in reading performance, particularly in text reading rate, accuracy and reading comprehension (Cain, & Bignell, 2014;Ghelani, Sidhu, Jain, & Tannock, 2004;Sesma et al, 2009). In general, difficulties in literacy acquisition associated with ADHD can be classified into three areas: weaknesses in text recall and comprehension (Sesma, et al, 2009), weaknesses in written expression, and weaknesses in language functioning 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation